Assessment of Development of Children in Diyala Province - Haider Asad Mohammad; Najdat Sh. Mahmood; Jalil I. Alezzi (Diyala Journal of Medicine, 2025)
Background: Developmental assessment is a systematic and comprehensive process that evaluates a child's progress across multiple domains of development to identify potential developmental delays or disabilities. Objective: This study aimed to assess the development of Iraqi children aged 2-60 months residing in Diyala province, compare it to other states, and estimate the prevalence of developmental delay. Patients and Methods: A total of 330 samples from children were recruited from Al-Batool Teaching Hospital for Maternity and Children over a six-month period, from October 2022 to March 2023. The Ages and Stages Questionnaire (ASQ3) was used to assess the children's development. The ASQ3 is a standardized tool used to screen for developmental delays in children aged 2-60 months. The ASQ3 scores are divided into three areas: white (normal development), black (delayed development), and gray (critical zone). Results: The study results showed that most of the children (97.6%) had normal development across all domains of development. However, 2.42% of the children had developmental delay, including two children (0.6%) with delayed speech and communication only and six children (1.8%) with global developmental delay in all areas. In addition, a proportion of children were situated within the gray area of the ASQ3 system, which indicates the need for further assessment to evaluate specific aspects of a child's development that may warrant closer attention. The proportion of children in the gray area ranged from 0% to 34.5%, depending on the development domain. Conclusion: The results of this study suggest that most children in Diyala province have normal development. However, a small percentage of children have developmental delays, and a proportion of children are situated in the critical area and need further assessment. Keywords: Developmental assessment, Developmental delay, Diyala, ASQ3.